Music in English Language Teaching - Kulić, Danijela G. (Collection of Papers of the Faculty of Philosophy in Priština, 2019)
The research subject in this paper is the role of music and musical ability of the students in teaching English as a foreign language. The theoretical frame of this paper encompasses findings in musical art that are related to foreign language teaching, as well as the analyses of the approach Suggestopedia by which the use of music in foreign language classes is recommended. It is assumed that the higher level of musical ability is in a direct relation with the capacity to acquire prosodic features of a foreign language, hence, students who recognize musical aptitude in themselves have better predispositions for foreign language pronunciation. General language ability, according to the results of the research that was conducted among young adolescents, positively correlates with the musical ability. Also, this paper presents multiple benefits that students could have from including music into ELT, and it suggests some techniques through which activation of both linguistic and musical abilities is possible. An example of an advanced language lesson, in which musical ability was triggered and musical content used as a leading idea, is presented in the paper. The cross-sectional study includes 376 younger adolescents, students of the VII and VIII grades of primary school and students of the I year of Gymnasium in Leskovac. The results of this research indirectly imply that music, instrumental and vocal, should be included into foreign language teaching, at all levels of studies through appropriate techniques.
Keywords: musical intelligence; Suggestopedia; English language; music; techniques; students